Plastic surgical trainees' perspectives toward burn surgery in Australia and New Zealand: Changes in the last 17 years?. Issue 8 (December 2021) - Sreedharan, S.; Cleland, H.; Lo, C.H.
Highlights: There is a worldwide shortage of burn surgeons. There has been an increase in interest amongst trainees in pursuing a career in burn surgery. Most common barriers to practising burn surgery remain unchanged: nature of burn operations, nature of burn care and on-call commitments. Inadequate exposure or training has evolved to present a bigger barrier. Half-time or sessional employment of burn surgeons is pragmatic and sustainable. Abstract: Introduction: An emerging amount of literature emphasises the ever-growing shortage of burn surgeons worldwide. Despite burn surgery being a fundamental competency in the Australia and New Zealand plastic and reconstructive surgery training curriculum, a perceived lack of interest amongst trainees exists. The aim of this study was to investigate Australasian plastic surgery trainees' interest in burn surgery as a career and compare with the Brown and Mills survey in 2004. Methods: An electronic survey was distributed to all Australian and New Zealand plastic and reconstructive surgery trainees during the March 2021 registrar trainee conference. This anonymous survey was adapted from the original survey conducted by Brown and Mills in 2004, with additional questions to determine the perceived importance of burns surgery as a subspecialty of plastic and reconstructive surgery, and to elicit possible solutions to the issue of workforce shortage. A reminder email was sent one month following the conference to improve the response rate. The survey was hosted by Survey Monkey (San Mateo, California, USA). Results: The survey was distributed to all 121 trainees and 71 (58.7%) responded. An increase in interest amongst trainees in pursuing a career in burn surgery was found, with 34 trainees (48.6% of respondents) interested, mostly on a half time or sessional basis. The three most common barriers to practising burn surgery remain unchanged, and were nature of burn operations, nature of burn care and on-call commitments; inadequacy of exposure or training ranked fourth. We found a strong overall response that burn surgery and burn care remained an important component of plastic and reconstructive surgery. Discussion: Inadequate exposure or training has evolved to present a bigger barrier in this study compared to a similar study conducted 17 years ago. Burn units and training bodies may offer additional job placements to address these feelings of insufficient exposure. Facilitating employment of burn surgeons on a half-time or sessional capacity is a sustainable model, and will arguably improve clinical service provision. Strong and early mentorship and allocation of commensurate resources and funding will help to address the high workload. Conclusions: Interest in burn surgery has improved over the last 17 years and the most common deterrents persist, namely nature of burn operations, nature of burn care and on-call commitments. However, many of these issues are modifiable or amenable to change. The opportunity exists for relevant stakeholders to address some of these concerns raised, and thereby addressing the issue of burn surgeon shortage.